Perancangan Sistem Informasi Web Pada Buku Tamu Dengan Mengunakan Metode Waterfall Di Ikest Muhammadiyah Palembang - Paray Theo Lonando, Paray Theo Lonando; Firdaus, Ahmad; Hakim, Ridwan (IKesT Muhammadiyah Palembang, 2024)
Utilization of information technology in all fields is a necessity to assist in operational activities in processing data quickly and precisely. Each IKesT Muhammadiyah Palembang guest book has assets in the form of guest reception data to support the activities of visiting visitors. Applications are a subclass of computer software that utilizes the computer's capabilities directly to perform a task that the user desires. This research aims: aims to design and develop a web-based guest book information system at IKesT Muhammadiyah Palembang using the Waterfall method. Method: The Waterfall method was chosen because of its structured and systematic development process, which includes the stages of needs analysis, design, implementation, testing and maintenance. The system developed is expected to replace the manual recording system that has been used. Results: the author will build a web information system for the IKesT Muhammadiyah Palembang guest book using a web application using Laravel, so that the process of recording guest data becomes more efficient, accurate and easy to access. In this way, it is hoped that it can improve the quality of service and guest data management at IKesT Muhammadiyah Palembang.